2017
DOI: 10.15407/tpwj2017.09.06
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of alloyed powders based on Fe<sub>3</sub>Al intermetallic for thermal spraying produced using mechanochemical synthesis method

Abstract: Results of experimental studies of the influence of the ratio of static and dynamic stresses on limit stresses and second critical brittleness temperature of butt welded joints with a crack on 09G2 and 12GN2MFAYu steels under the conditions of room and low (to-80 °C) temperatures are analyzed. It is found that at the specified temperature the dynamic component of critical stress decreases linearly with increase of static stress. It is shown that decrease of limit stresses and increase of the second critical br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The characteristics of the MCS powders used in work for investigating the coating formation process during plasma spraying are shown in Table 2 [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the MCS powders used in work for investigating the coating formation process during plasma spraying are shown in Table 2 [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…At present, one of the ways to obtain composite intermetallic powders of the Fe-Al system for thermal spraying is the mechanochemical synthesis method (MCS) [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The physical-chemical processes occurring during the formation of particles of iron intermetallics based on Fe 3 Al alloyed with Cr, Zr, Mg, La, and Ti under conditions of mechanochemical synthesis were studied in works [16,17]. It was found that the mechanism of formation of both unalloyed Fe 3 Al particles and particles of alloyed powders based on this intermetallic compound consists of a number of successive stages: formation of conglomerates from a mixture of initial Fe powders and aluminum alloys; formation of solid solutions of alloying elements based on the Fe 3 Al lattice or an Al solid solution in the FeTi lattice; transformation of solid solutions into single-phase products Fe 3 Al(Cr,Zr), Fe 3 Al(Mg), Fe 3 Al(Mg,La) and (Fe,Ti) 3 Al with nanodispersed structure (coherent scattering region 10-30 nm).…”
Section: Introductionmentioning
confidence: 99%